2023
DOI: 10.1038/s41467-023-38150-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical imaging reveals diverse functions of tricarboxylic acid metabolites in root growth and development

Abstract: Understanding how plants grow is critical for agriculture and fundamental for illuminating principles of multicellular development. Here, we apply desorption electrospray ionization mass spectrometry imaging (DESI-MSI) to the chemical mapping of the developing maize root. This technique reveals a range of small molecule distribution patterns across the gradient of stem cell differentiation in the root. To understand the developmental logic of these patterns, we examine tricarboxylic acid (TCA) cycle metabolite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“… Timeline for the development of techniques that have driven research on plant secondary metabolites. Pictures are from: MS imaging ( Zhang et al 2023 ); FRET ( Herud-Sikimić et al 2021 ); mutant analysis ( Adiji et al 2021 ); synthetic biology ( Brophy et al 2022 ); and single-cell transcriptomics ( Nolan et al 2023 ). The picture bottom left is a vintage lithograph showing the white willow, Salix alba (original book source: Prof. Dr Otto Wilhelm Thomé, Flora von Deutschland, Österreich und der Schweiz 1885, Gera (Germany)—public domain, https://commons.wikimedia.org/w/index.php?curid=2358667 ).…”
Section: The Era Of Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“… Timeline for the development of techniques that have driven research on plant secondary metabolites. Pictures are from: MS imaging ( Zhang et al 2023 ); FRET ( Herud-Sikimić et al 2021 ); mutant analysis ( Adiji et al 2021 ); synthetic biology ( Brophy et al 2022 ); and single-cell transcriptomics ( Nolan et al 2023 ). The picture bottom left is a vintage lithograph showing the white willow, Salix alba (original book source: Prof. Dr Otto Wilhelm Thomé, Flora von Deutschland, Österreich und der Schweiz 1885, Gera (Germany)—public domain, https://commons.wikimedia.org/w/index.php?curid=2358667 ).…”
Section: The Era Of Biosynthesismentioning
confidence: 99%
“…The figure from Brophy et al (2022) is reprinted with permission from AAAS. Other images are our own or licensed under a Creative Commons Attribution License (CC BY, https://creativecommons.org/licenses/by/4.0/ ) by Zhang et al (2023) , Herud-Sikimić et al (2021) , and Nolan et al (2023) . EST, expressed sequence tag; FLIM, fluorescence lifetime imaging microscopy.…”
Section: The Era Of Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between metabolic messengers and their target proteins across tissues can be characterised with increasingly high resolution by developments in spatial and single cell metabolomics, although sensitivity limitations might currently restrict the detection of InsP or PP-InsP species in a single cell [138,139]. Desorption electrospray ionisation mass spectrometry imaging has recently mapped lipids, metabolites and carbohydrates across root tips to detect variations in TCA cycle intermediates across root meristem and differentiation zone, that did not correlate with changes in ATP levels [140]. Similar techniques could be applied to detect gradients for other metabolic messengers across tissues and development.…”
Section: Signalling Moleculesmentioning
confidence: 99%
“…Both plants and animals can vary division rates by controlling the passage through G1 and G2 checkpoints, which are often regulated by metabolites 9,25 . For example, it was recently shown that tricarboxylic acid cycle metabolites may regulate root growth and development 26 . In addition, reactive oxygen species (ROS) have a role in controlling division rates along the root axis 27 .…”
Section: Introductionmentioning
confidence: 99%